Things that Travelled Mediterranean Glass in the First Millennium CE (University College London, 2018)
Recent research has demonstrated that, in the Roman, Late Antique, Early Islamic and Medieval worlds, glass was traded over long distances, from the Eastern Mediterranean, mainly Egypt and Israel, to Northern Africa, the Western Mediterranean and Northern Europe. Things that Travelled, a collaboration between the UCL Early Glass Technology Research Network, the Association for the History of Glass and the British Museum, aims to build on this knowledge. Covering all aspects of glass production, technology, distribution and trade in Roman, Byzantine and Early Medieval/Early Islamic times, including studies from Britain, Egypt, Cyprus, Italy and many others, the volume combines the strengths of the sciences and cultural studies to offer a new approach to research on ancient glass. By bringing together such a varied mix of contributors, specialising in a range of geographical areas and chronological time frames, this volume also offers a valuable contribution to broader discussions on glass within political, economic, cultural and historical arenas.